The extent to which the curricula of the Department of Mathematics, College of Education, Tripoli, align with the labor market requirements from the perspective of faculty members and graduates (Sebha University Conference Proceedings, 2025)
The study investigates the alignment of the Department of Mathematics' curriculum at the Faculty of Education in Tripoli to the labour market requirements from the perspective of faculty members and graduates. We employed the descriptive approach and the questionnaire as the primary research tool. The questionnaire was distributed to a sample of (47) participants, including (14) faculty members and (33) graduates. The finding indicates that the level of knowledge, skills, and training provided to students was average. However, graduates demonstrate a high ability to meet the labour market demand. The study also highlights a strong need to update the curriculum to keep pace with advancements in mathematics and labour market needs. Additionally, the study finds no statistically significant differences in participants’ responses based on gender, qualification, capacity, and years of experience. Based on these findings, the study recommends updating the Mathematics Department’s curriculum to align with regional and global market development, emphasising enhancing students’ applied skills and strengthening the connection between coursework and labour market needs